Incorporation of conjugated linoleic and alpha linolenic fatty acids into Pimedolus maculatus fillets - Zanqui,Ana Beatriz (2013)
The objective of this study was to investigate the fatty acid composition of Pimedolus maculatus fillets of fish fed with different diets. The fish were submitted to an adaptation period (over 30 days) and fed only a control diet (diet I). After this period, the fish were divided into two groups: one group received a diet enriched with flaxseed oil (diet II), and the other received a diet enriched with conjugated linoleic acid (CLA) (diet III). Subsequent collections were undertaken after 25 and 50 days. Compared to the control samples, fish fed diet II showed an increase in concentrations of total fatty acid omega-3 (n-3) in the fillets, with an improvement ratio of n-6/n-3. The incorporation of CLA into fish fed diet III was successful. Supplementing the diet of Pimedolus maculatus with CLA and flaxseed oil led to improvements in nutritional quality and fatty acid profile of the fish fillets.